Directional cloverleaf antenna for unmanned aerial vehicle (UAV) application - M.S. Safaron; H.A. Majid; B.A.F. Esmail; A.S.Ab. Ghafar; F.A. Safarudin; M.F. Ismail; F. Zubir; M.A. Abdullah (Institute of Advanced Engineering and Science, 2019)
3-blade and 4-blade cloverleaf antennas operating at 2.45 GHz have been proposed. In order to achieve directional radiation pattern and high gain, reflector is incorporated to the proposed antennas. The proposed antennas have an average gain of 2.37 dBi while the proposed antennas with reflector have an average gain of 6.38 dBi. The dimension of the proposed antenna is compact enough to be mounted on an unmanned aerial vehicle (UAV). Simulated and measured results are used to demonstrate the performance of the antenna. The simulated and measured return losses, together with the simulated radiation patterns, are presented and compared.